Type 2 Diabetes Contributes to Altered Adaptive Immune Responses and Vascular Inflammation in Patients With SARS-CoV-2 Infection - Singh, Manpreet; Barrera Adame, Obed; Nickas, Michael; Robison, Jeremiah; Khatchadourian, Christopher; Venketaraman, Vishwanath (Frontiers in Immunology, 2022)
SARS-CoV-2, which initially emerged in November of 2019, wreaked havoc across the globe by leading to clinical acute respiratory distress syndrome and continues to evade current therapies today due to mutating strains. Diabetes mellitus is considered an important risk factor for progression to severe COVID disease and death, therefore additional research is warranted in this group. Individuals with diabetes at baseline have an underlying inflammatory state with elevated levels of pro-inflammatory cytokines and lower levels of anti-inflammatory cytokines, both of which cause these individuals to have higher susceptibility to SARS- CoV2 infection. The detrimental effects of SARS-CoV-2 has been attributed to its ability to induce a vast cell mediated immune response leading to a surge in the levels of pro-inflammatory cytokines. This paper will be exploring the underlying mechanisms and pathophysiology in individuals with diabetes and insulin resistance making them more prone to have worse outcomes after SARS- CoV2 infection, and to propose an adjunctive therapy to help combat the cytokine surge seen in COVID-19. It will also look at the immunomodulatory effects of glutathione, an antioxidant shown to reduce immune dysregulation in other diseases; Vitamin D, which has been shown to prevent COVID-19 patients from requiring more intensive care time possibly due to its ability to decrease the expression of certain pro-inflammatory cytokines; and steroids, which have been used as immune modulators despite their ability to exacerbate hyperglycemia.